Human speech reduces pygmy marmoset (Cebuella pygmaea) feeding and resting at a Peruvian tourist site, with louder volumes decreasing visibility. Issue 4 (28th March 2019) - Sheehan, Rebecca L.; Papworth, Sarah
Abstract: Although potentially beneficial in terms of raising awareness and conservation funding, tourist visitation of wild primates can have negative impacts on visited groups. Tourism‐generated noise is a relatively understudied facet of ecotourism research, and the effects of tourist‐generated speech on free‐ranging, wild primates has never been explored previously. This study investigates the behavioral responses of 10 groups of pygmy marmosets ( Cebuella pygmaea ) to human speech. Through the use of an experimental playback study using recorded human speech, we show that pygmy marmosets within the Tamshiyacu‐Tahuayo Reserve, Peru, are significantly less visible, and often move completely out of sight after louder playbacks. Although no consistent differences were found in other behaviors with playback duration and volume, playbacks of human speech tended to increase the amount of time individuals were alert and decrease feeding and resting behaviors. Our results demonstrate that human speech can alter the behavior of visited primates, and identifies a decrease in primate visibility within the increasing volume. As all trials in this study took place near a marmoset group's feeding tree, moving out of sight from the visible study area is a particularly energetically costly behavior, and also has a negative effect on visitor enjoyment as it limits the time that they are able to view the target species. This response was not observed (nor was any other consistent behavior change) in control trials where the marmosets were exposed to human presence but not to speech, suggesting that negative tourist impacts can be reduced by encouraging tourists to refrain from speaking in the presence of visited primate groups. Abstract : When exposed to playbacks of a human voice, wild pygmy marmosets were more likely to respond by moving out of sight when playbacks were louder, and never moved out of sight when the experimenters were present but no human voice was played.